PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS PERMAINAN FAMILY 100 UNTUK MENUMBUHKAN KERJASAMA SISWA DALAM PEMBELAJARAN IPAS MATERI BENTANG ALAM KELAS IV SDN DUKUH KUPANG V SURABAYA - Agis Salsabilla, Shinta; Suprhiatien, Titien; Jarmani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to develop an interactive learning medium based on the "Family 100" game that is valid, practical, and effective in fostering cooperation among fourth-grade students in Science and Social Studies (IPAS), specifically on the topic of Landscapes. The main problem underlying this research is the conventional teaching method (lectures) and the lack of interactive media, which result in low student collaboration skills. The research method used is Research and Development (R&D) with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The results showed that the developed media is highly feasible, with a media expert validation percentage of 97,14% and material expert validation of 100%. This media is proven to trigger active interaction and group discussion through a game mechanism that requires team consensus in answering popular questions.